KATABEL Flashcards for Fable-Based Dance Learning in Primary School - Marcella Nadya Irafany; Deasylina da Ary (Women, Education, and Social Welfare, 2026)
Dance instruction in primary school requires learning media that make movement concepts concrete, engaging, and usable for young learners. This study developed KATABEL, a fable-based dance flashcard medium, and examined its feasibility and preliminary effectiveness in Grade 4 dance learning. The study employed research and development using the ADDIE framework and involved 29 students at a public primary school in Pati Regency, Indonesia. KATABEL combines animal-fable narratives, illustrations, QR-code-linked movement videos, and prompts for imitating, adapting, sequencing, and presenting movement. Feasibility was assessed by content and media experts; implementation evidence was obtained through sequential small-group (n = 6) and large-group (n = 23) pretest-posttest trials. Content and media validation yielded 93% and 96%, respectively, placing the product in the highly feasible category. Shapiro-Wilk results supported normality, and paired-sample tests indicated significant gains in both trials (small group: t = -8.174, p < .001; large group: t = -18.325, p < .001). Mean normalized gains were 0.6879 and 0.7366. KATABEL offers a low-cost, human-centered physical-digital learning resource that supports movement exploration, participation, and equitable access to primary arts learning.